2021
DOI: 10.1177/10892532211045765
|View full text |Cite
|
Sign up to set email alerts
|

Low Mean Arterial Pressure During Cardiopulmonary Bypass and the Risk of Acute Kidney Injury: A Propensity Score Matched Observational Study

Abstract: Introduction Low mean arterial pressure (MAP) periods occur frequently during cardiopulmonary bypass (CPB), and their management remains controversial. Our aim was to correlate MAP during CPB with the occurrence of post-operative acute kidney injury (AKI), considering two different parameters: consecutive and cumulative low MAP periods. Methods Single-centre observational retrospective study including 250 patients submitted to non-emergent aortic valve replacement, with tepid to mild hypothermia (not below 32°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Presentations and the temporal transitions between the different phases of renal dysfunction can follow multiple trajectories: early dysfunction with complete recovery, late dysfunction with late recovery, late onset of dysfunction, biphasic dysfunction, partial recovery, and no recovery (Figure 1). Velho et al found that 5 minutes of hypotension (MAP <50mmHg) could lead to AKI (by AKIN criteria) 11 in a single center retrospective study. Interesting about the study was that pump flow was maintained above 2.4 L/min/m2, and hematocrit was above 24%.…”
mentioning
confidence: 99%
“…Presentations and the temporal transitions between the different phases of renal dysfunction can follow multiple trajectories: early dysfunction with complete recovery, late dysfunction with late recovery, late onset of dysfunction, biphasic dysfunction, partial recovery, and no recovery (Figure 1). Velho et al found that 5 minutes of hypotension (MAP <50mmHg) could lead to AKI (by AKIN criteria) 11 in a single center retrospective study. Interesting about the study was that pump flow was maintained above 2.4 L/min/m2, and hematocrit was above 24%.…”
mentioning
confidence: 99%